Phytochemical assessment, elemental composition, and biological kinetics of Foeniculum vulgare Mill. stalks - Covenant E. Ogbonna; Doga Kavaz; Yemi A. Adekunle; David B. Olawade (Elsevier, 2024)
Introduction: The essential oil of Foeniculum vulgare (Fennel) has been extensively studied for phytochemical and elemental compositions, biochemical significance, and biological activities. However, the literature has a dearth of information on the Fennel stalk as a potential source of antioxidant and antibacterial agents. This study aimed to evaluate the phytochemical and elemental composition of Fennel stalks and also, to investigate the kinetic DPPH scavenging property and antibacterial activity of Fennel stalk extracts. Methods: Fennel aqueous extract (FVAE) was prepared by mixing of powdered fennel stalks with sterile distilled water, followed by heating and filtration. Methanol (FVME) and ethanol (FVEE) extracts of F. vulgare were prepared by macerating the stalk with respective solvents, followed by filtration. Gas chromatography-mass spectrometry (GC-MS) analysis, Fourier Transform Infrared Spectroscopy (FTIR), determination of total phenols, and X-ray fluorescence were conducted to analyze the chemical composition of the extracts. Biological activities, including DPPH scavenging and antimicrobial activity against Methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli, were evaluated through spectrophotometric methods and well diffusion assay, respectively. Results: The GCMS analysis revealed 15 compounds including anozol, myristyl iodine, flexiricin, dutadrupine, cycloheptaciloxane, neophytadiene, phthalic acid, and ribitol. Some of these compounds have not been reported from this plant before. FTIR analysis suggested hydroxyl (OH), alkane (CH), carbonyl (C = O), aromatic (C = C), and ether (CO) functional groups in the Fennel extracts. X-ray fluorescence identified elements including titanium, chromium, manganese, iron, nickel, copper, zinc, rubidium, and strontium. The ethanol extract had higher total phenolic content (72.45±0.01 mg GAE/g) than the aqueous (54.3 ± 0.01 mg GAE/g) and methanol (51.3 ± 0.01 mg GAE/g) extracts. In addition, a high% DPPH scavenging activity was observed in the ethanol extract (85.1 %) compared to that of ascorbic acid (96.2 %). Fennel's stalks methanol extract showed significant inhibition against the growth of E. coli 0157 and Methicillin-resistant Staphylococcus aureus B-4420, having zones of inhibition diameters of 16 mm and 13 mm, respectively. This is similar to what was observed for chloramphenicol and azithromycin. Conclusion: The current study has demonstrated that Fennel stalks contain potentially useful antioxidant and antibacterial properties, in addition to the well-studied essential oil of its fruits and seeds.